2022
DOI: 10.3390/su142315552
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Renewable and Nonrenewable Energy Usage and Technological Innovation on Environmental Sustainability: Evidence from QUAD Economies

Abstract: The following study examined how energy use and technological advancement impacted environmental sustainability in QUAD (US, Japan, Australia, and India) economies between 1991 and 2021. The study considers the generation of renewable energy, fossil fuel use, and the effects of economic expansion on environmental sustainability. The research used the moment quantile regression technique based on the outcomes of slope heterogeneity, cross-sectional dependence, and the order of the unit-root by the using second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Especially in the absence of appropriate policies and legislation, regional economic cooperation may lead to increased carbon emissions [26], thus jeopardizing the sustainability of the environment. Therefore, technological innovation [27], technology transfer [28], and the widespread use of renewable energy [29] are significant. Based on these findings, we recognize the importance of promoting environmental sustainability through regional integration policies and need to explore more deeply the potential mechanisms of the specific impact of regional integration policies on carbon emissions.…”
Section: Literature Gapmentioning
confidence: 99%
“…Especially in the absence of appropriate policies and legislation, regional economic cooperation may lead to increased carbon emissions [26], thus jeopardizing the sustainability of the environment. Therefore, technological innovation [27], technology transfer [28], and the widespread use of renewable energy [29] are significant. Based on these findings, we recognize the importance of promoting environmental sustainability through regional integration policies and need to explore more deeply the potential mechanisms of the specific impact of regional integration policies on carbon emissions.…”
Section: Literature Gapmentioning
confidence: 99%
“…Furthermore, (Raihan et al, 2023) focus on the pressing issue of CO2 emissions in Indonesia, assessing the potential impact of economic growth, RE utilization, technical advancement, and forest cover on emissions from 1990 to 2020. Employing the Dynamic Ordinary Least Squares (DOLS) approach, the study finds that economic development corresponds to a 1.17% increase in CO2 emissions (Imran et al, 2022). Conversely, a 1% rise in RE usage is linked to a 1.40% decrease, technical innovation is associated with a 0.17% decrease, and an augmented forest cover correlates with a 3.94% reduction in CO2 emissions.…”
Section: Renewable Energy and Its Impactmentioning
confidence: 99%
“…Many studies have revealed that innovation can contribute significantly to sustainability by retaining the ecosystem and providing innovative solutions to environmental problems. For example, after reviewing the effects of energy use and technology innovation on environmental sustainability from 1991 to 2021 for the USA, Australia, Japan, and India, Imran et al [6] found that technological innovation enhances environmental sustainability. Open innovation is endorsed by some studies as the right way to develop and deliver more sustainable and marketable products [7,8].…”
Section: Introductionmentioning
confidence: 99%